Peculiarities of the Organizational Changes in Higher Educational Institutions - Tsay, Viktoriya; Kunanbayeva, Dana; Sataev, Sanat; Skiba, Marina (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018DO - 10.14505//jarle.v9.1(31).38, 2018)
The Universities in Kazakhstan are tasked to reach the world level in the development of science and education, which show a clear need for numerous innovations. Against the backdrop of the rapid changes that are taking place today in all spheres of our society, the higher professional education system’s task of innovative development becomes extremely important for achieving socially significant positive results. The development of new approaches is required, the main goal of implementation of which is a sharp increase in the quality of educational activity, the development of science and technology.In this article, the author reviews the main directions of the theory of change management, examines the main directions of changes occurring in the university’s process of introducing innovative educational technologies into the educational process, and there has been developed a model for introducing changes in higher education institutions.